2016
DOI: 10.1097/prs.0000000000001907
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes following Traumatic Optic Neuropathy

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
(35 reference statements)
0
22
0
Order By: Relevance
“…Direct TON results from anatomical damage to the optic nerve by penetrating trauma or bony laceration. Indirect TON results from optic nerve damage secondary to compression or swelling from transmission of high velocity force from a distant site 1417. This transmission of force is highlighted by patients 9, 18, and 27 of Group 1, who demonstrate indirect TON as a result of sheer force transmitted to the optic nerve contralateral to the side of fracture(s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct TON results from anatomical damage to the optic nerve by penetrating trauma or bony laceration. Indirect TON results from optic nerve damage secondary to compression or swelling from transmission of high velocity force from a distant site 1417. This transmission of force is highlighted by patients 9, 18, and 27 of Group 1, who demonstrate indirect TON as a result of sheer force transmitted to the optic nerve contralateral to the side of fracture(s).…”
Section: Discussionmentioning
confidence: 99%
“…Recovery of visual acuity was not recorded for this study. Many trauma patients with TON often do not return for follow-up due to expiration or choices beyond our control, making outcomes difficult to document 14. If an appropriately powered patient population could be followed up, a future prospective study might correlate fracture pattern with posttraumatic visual acuity to identify which fracture patterns portend a more favorable prognosis and would contribute strongly to the literature, perhaps changing practice patterns.…”
Section: Discussionmentioning
confidence: 99%
“…20,25) The site of injury causing blindness is typically the forehead or supraorbital ridge, and less commonly may be the temporal region. 20,23) of vision. According to a study by Ansari 2) , in which a total of 2,503 patients were enrolled, retrobulbar hemorrhage was thought to be the primary mechanism of blindness, followed by direct damage to the eyeball.…”
Section: Classification Of Tonmentioning
confidence: 99%
“…20,25) The site of injury causing blindness is typically the forehead or supraorbital ridge, and less commonly may be the temporal region. 20,23) Recently, Magarakis et al 19) systematically reviewed the literature to identify specific facial bone fracture patterns associated with ocular injury, including blindness. The authors found that zygomatic-maxillary complex fractures were the most common type of injury complicated by loss of vision.…”
Section: Classification Of Tonmentioning
confidence: 99%